2016
DOI: 10.4081/aiol.2016.5682
|View full text |Cite
|
Sign up to set email alerts
|

Results of the first Wave Glider experiment in the southern Tyrrhenian Sea

Abstract: <p>A wave-propelled autonomous vehicle (Wave Glider) instrumented with a variety of oceanographic and meteorological sensors was launched from Gulf of Naples on the 12<sup>th </sup>of September 2012 for a two-week mission in the Southern Tyrrhenian Sea. The main objective of the mission was a preliminary evaluation of the potential of commercial autonomous platforms to provide reliable measurements of sea surface parameters which can complement existing satellite based products moving from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 33 publications
1
26
0
Order By: Relevance
“…Its typical water column yields a three-layer system composed of the surface Atlantic Water, the Levantine Intermediate Water (LIW), and the Tyrrhenian Deep Water. The intensity of the cyclonic surface and intermediate circulation decreases from the boundaries to the center of the basin, while the deep circulation is very weak (Astraldi & Gasparini, 1995;Aulicino et al, 2016;Hopkins, 1988;Menna & Poulain, 2010). The Tyrrhenian basin is considered a merging collector of both the Eastern and Western signals (Astraldi & Gasparini, 1995), receiving a considerable amount of eastern waters, mainly the LIW (Sparnocchia et al, 1999) as well as Atlantic Water and Western Mediterranean Deep Water (WMDW) of western origin (Schroeder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Its typical water column yields a three-layer system composed of the surface Atlantic Water, the Levantine Intermediate Water (LIW), and the Tyrrhenian Deep Water. The intensity of the cyclonic surface and intermediate circulation decreases from the boundaries to the center of the basin, while the deep circulation is very weak (Astraldi & Gasparini, 1995;Aulicino et al, 2016;Hopkins, 1988;Menna & Poulain, 2010). The Tyrrhenian basin is considered a merging collector of both the Eastern and Western signals (Astraldi & Gasparini, 1995), receiving a considerable amount of eastern waters, mainly the LIW (Sparnocchia et al, 1999) as well as Atlantic Water and Western Mediterranean Deep Water (WMDW) of western origin (Schroeder et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed the advantages of multiplatform ocean monitoring over different scales, including mesoscale, and at different latitudes [31][32][33][34][35][36][37]. Recent experiments demonstrated that combining new technologies for in situ data collection, mainly autonomous underwater vehicles (AUVs), and reliable satellite data in the AB (e.g., [12,38,39]), provides useful contributions to properly address state-of-the-art scientific challenges [40][41][42]. AUVs allow the collection of high resolution physical and biochemical data along the water column from surface to 975 m depth [17], while their use in combination with remote sensing observations provides a better understanding of basin-scale processes, such as those influencing the southwestern Mediterranean Sea dynamics [38,43].…”
Section: Introductionmentioning
confidence: 99%
“…To this aim, frequent dedicated observations at higher horizontal and vertical resolution, along the water column, are essential (Pascual et al, 2017). Multi-platform monitoring strategies, which enable the integration of data from satellites, Autonomous Underwater Vehicles (AUV) and numerical models, have already demonstrated their capabilities in the assessment of oceanographic processes in different regions of the global ocean, such as the Atlantic Ocean (Shcherbina et al, 2015) and the Mediterranean Sea (Carret et al, 2018;Troupin et al, 2018;Pascual et al, 2017;Aulicino et al, 2016). The value of these is improved when implemented along repeated monitoring lines coincident with the satellite groundtracks (Aulicino et al, 2018).…”
Section: Introductionmentioning
confidence: 99%